Genetic mapping of pancreatic cancer by targeted next-generation sequencing in a cohort of patients managed with nab-paclitaxel-based chemotherapy or agents targeting the EGFR axis: a retrospective analysis of the Hellenic Cooperative Oncology Group (HeCOG). Issue 5 (18th September 2019) - Zarkavelis, George; Kotoula, Vassiliki; Kolliou, Georgia-Angeliki; Papadopoulou, Kyriaki; Tikas, Ioannis; Karavasilis, Vasilios; Samantas, Epaminontas; Dervenis, Christos; Efstratiou, Ioannis; Nicolaou, Irene; Apessou, Dimitra; Kafiri, Georgia; et al.
Abstract : Pancreatic cancer is one of the most fatal malignancies ranking fourth among the leading causes of cancer death with diagnosis at late stages carrying a dismal prognosis. The aim of our retrospective study was to describe the nature and the incidence of gene mutations and genomic instability in advanced pancreatic adenocarcinomas of a Greek patient population fully annotated with clinicopathological data. We used a targeted next-generation sequencing (NGS) panel encompassing genes commonly mutated in pancreatic tumours in a patient population managed with either nab-paclitaxel regimens or targeted compounds modulating the epidermal growth factor receptor (EGFR)/AKT/mTOR axis. We identified KRAS, TP53, SMAD4 and CDKN2A as being the most prevalent mutations in the study population with the exception of an intriguingly lower incidence regarding KRAS mutants. Homologous recombination gene mutations were found to be mutually exclusive with CDKN2A mutations. The coexistence of both KRAS and TP53 mutation seems to adversely affect the outcome of the patients whether treated with targeted therapy against EGFR/Akt/mTOR axis or cytotoxic drugs. The poor prognosis observed, correlated to late presentation, specific molecular mutations and to high mutational load warrant prospective validating studies and research into the mechanistic pathophysiology of pancreatic tumours for more effective therapeutic targeting.